Influence of Fiber Type on Low-Temperature Fracture Performance of Presawed Asphalt Mixture Beams - Jinrong Wu; Rongbao Hong; Chenbin Gu (Advances in Materials Science and Engineering)
In order to improve the durability of asphalt pavement, low-temperature fracture performance of AC-13 asphalt mixture with different fiber types were studied by three-point bending fracture test under different temperatures and presawed positions. Test results show that the improvement effect of basalt fiber is obvious and stable. The improvement effect of polyester fiber is not obvious to resist I crack, and the resistance effect of I-II compound crack is obvious. Lignin fiber mixed in the asphalt mixture has no obvious effect on improving the crack resistance property under low temperature. Fiber cooperated with asphalt mixture can improve the ability of low-temperature fracture performance, while the improvement degree is effected by fiber type. Low-temperature fracture performance of asphalt mixture improves with the increase of temperature within a certain temperature range. The presawed position has significant effect on the low-temperature fracture performance of asphalt mixture. The larger the horizontal distance of the presawed position and center load is, the stronger the low-temperature fracture performance of asphalt mixture presents.